Practical teaching programme online: Overcoming communication issues - Noor Shah, Mohd Salleh (Elsevier, 2001)
A teaching practicum module is normally the learning activity that obligates student–teachers to be sent to different schools and localities, to experience teaching, or be trained in the real-world environment. Because of geographical boundaries, often times peer-to-peer and student–instructor communications are complicated and hard to manage. This has been a perennial problem for all teacher training schools, be it in local teacher training colleges or teacher education programs at the universities in Malaysia. One solution employed by the teacher education programme at Universiti Malaysia Sarawak (UNIMAS) is by using a Web-based learning environment. Student–teachers are now able to meet and discuss issues and challenges that they faced, thus overcoming geographical limits. As they are able to act and solve problems at Internet speed, many thrive on ideas and suggestions provided by the online community. This paper reports the numerous advantages obtained by the employment of a Web-based learning environment as a tool in overcoming communication problems faced in the traditional setting of a practical teaching programme. An unexpected outcome was also noted amongst the non-contributors to the discussion online whom the author called the silent participant. Nevertheless, for many of us involved in teacher education, the possibility of a web-based ‘communication site’ during a practical teaching course is a dream come true.